(untitled) (Revista de Medicina Clinica, 2023)
Clinical Snapshot on "Furunculous Myiasis in Young Adults with Psoriasis, Description of an Entity Associated with Underdevelopment in the Americas" presented in volume 7 issue 1 of 2023 of Revista de Medicina Clínica.